Circulating levels of acute-phase proteins, heat shock protein 70, and corticosterone in the serum of developing chick embryos and newly hatched broiler chicks - Ahmad Hanafi Sulong; Idrus Zulkifli; Suriya Kumari Ramiah; Eric Lim Teik Chung; Elmutaz Atta Awad; Awis Qurni Sazili (Italian Journal of Animal Science, 2021)
Acute-phase proteins (APPs) are known to mediate the body's first line of defence against external insults in poultry and there is a growing interest to use the proteins to diagnose poultry health and physiological status. However, there is no report describing APPs during the prenatal and neonatal stages in poultry. The objectives of the study were to determine the presence and circulating concentrations of APPs in the embryos, and newly hatched chicks. Cobb 500™ eggs were incubated under a standard condition for 21 d. Blood samples were collected from embryos on days 14 (ED 14), 16 (ED 16), and 18 (ED 18) of incubation as well as newly hatched chicks to determine serum levels of corticosterone (CORT), alpha-1 acid glycoprotein (AGP), ceruloplasmin (CPN), and heat shock protein 70 (Hsp70). Both CORT and CPN showed a dramatic increase from ED 14 to ED 16 (p < .0001) but declined at ED 18 (p = .0004). The newly hatched chicks had elevated CORT (p < .0001) and CPN (p < .0001). Serum AGP rose from ED 14 to ED 18 and was followed by a sharp fall in the newly hatched chicks (p = .0074). Serum concentrations of Hsp70 were consistently elevated across the embryos' developmental stage and remained high in the newly hatched chick (p < .0001). In conclusion, APPs were detected in the blood of chicken embryos and neonates for the first time and the levels vary according to the development stage. These results have raised the need to better understand the physiological relevance of APPs in developing embryos and newly hatched chicks.Highlights Acute-phase proteins were detected and quantified in the circulation of developing chicken embryos and newly hatched chick for the first time. The magnitude of production of acute-phase proteins varied according to developmental stages. Acute-phase proteins may be of physiological relevance for the developing chicken embryos.